Enhancing Student Creativity: Vice Principals' Training for Effective Work Programs in Pekanbaru: Memperkuat Kreativitas Siswa: Pelatihan Wakil Kepala Sekolah untuk Program Kerja Efektif di Pekanbaru - Nurfaisal Nurfaisal; Ali Asfar; Adi Rahmat; Ardiya (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Community Service: Training for Student Affairs Vice Principals' Work Program Development in Pekanbaru. This outreach activity was conducted by the faculty members of the Master's Program in Management at the Graduate School of Universitas Lancang Kuning. The participants included 18 vice principals from state high schools (SMAN), 10 from vocational schools (SMKN), and 4 from state Islamic schools (MAN), totaling 32 vice principals. The objective of this initiative was to enhance the competencies of student affairs vice principals in addressing and anticipating various teenage misbehaviors prevalent in today's society. The training aimed to foster the creation of effective work programs that would nurture students' character and creativity while promoting the development of scientific and technological knowledge that benefits the local community, nation, and country. The benefits derived from this program included the formulation of daily, weekly, monthly, and annual work programs for student affairs vice principals in SMAN, SMKN, and MAN throughout Pekanbaru, with a focus on character building, student behavior, and creativity, while also preserving Riau Malay Culture. Furthermore, the training aimed to proactively address the impact of media on adolescent behavior, especially among secondary school students. The anticipated outcomes of this training endeavor aimed to make a positive contribution to the local community, nation, and country at large.